Doppler sonar analysis of swallowing sounds in normal pediatric individuals - Cagliari,Cibele Fontoura (2009)
Among the methods for assessing swallowing sounds - videofluoroscopy modified barium study, fiberoptic swallowing endoscopy, neck auscultation through a microphone, accelerometer and, more recently, the Doppler sonar - we have chosen the latter. AIM: to analyze swallowing sounds by cervical auscultation using Doppler sonar, in a population between 2 and 15 years without oro-pharyngeal dysfunction. STUDY DESIGN: cross-sectional historical cohort. MATERIALS AND METHODS: we investigated 90 individuals in Curitiba (2006/2007). The population was separated by age into 3 groups: from 2 to 5 years, from 5 to 10 years of age and from 10 to 15 years of age. We obtained the average values for frequency, intensity and swallowing duration for saliva, liquid and pasty foods). RESULTS: objective and measurable data were obtained. Significance related to gender was found in certain age groups and consistencies, under all the studied variables, except swallowing time. CONCLUSION: neck auscultation using Doppler sonar is a sensitive method to detect swallowing sounds. There was swallowing interference associated with saliva and the other tested food types and with the biological development of the age range being studied. It is an easy to apply method, not expensive and non-invasive.